The Gestational Triad: A Framework for Integrating Pharmacovigilance, Clinical Care and Community Health in Maternal Medicine - Ain-Ul Momina, Ayesha Tahir, Saddiqa Hassan, Nadeem Akhtar Korai, Usman Saeed, Mubasher Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: This study aimed to develop and evaluate a practical, multidisciplinary framework—"The Gestational Triad"—for improving maternal health outcomes by systematically integrating pharmacovigilance (medication safety), evidence-based clinical obstetrics, and community-centered public health strategies. Study Duration: March 2022 to March 2023. Study Place: Niazi Medical & Dental College, Sargodha. Methodology: A mixed-methods design was employed: 1) A retrospective analysis of 1,500 antenatal and postpartum electronic health records (EHRs) to audit drug prescribing patterns and related maternal/neonatal outcomes; 2) Establishment of a prospective, active pharmacovigilance reporting system for obstetric drugs; 3) Focus group discussions (FGDs) and structured interviews with 30 community health workers (CHWs) and 15 obstetricians to identify systemic barriers; and 4) The pilot implementation of the "Gestational Triad" protocol in two intervention community health centers, compared with two control centers. Results: The EHR audit revealed 22% of pregnant women were prescribed medications from FDA Category C, D, or X, with incomplete documentation of risk-benefit counseling in 68% of cases. The active surveillance system identified nausea and drowsiness as the most common adverse drug reactions (ADRs) to first-line antiemetics. CHWs identified lack of medication knowledge and fear of side effects as top adherence barriers. Pilot sites implementing the Triad framework showed a 40% increase in documented risk counseling, a 25% improvement in adherence to iron-folic acid supplementation, and a 15% reduction in self-reported minor ADRs compared to control sites. Conclusion: The "Gestational Triad" framework demonstrates feasibility and initial effectiveness in creating a synergistic workflow between drug safety monitoring, standardized clinical practice, and community-based support. Its implementation fosters more rational prescribing, empowered patients, and safer medication use during pregnancy and postpartum, offering a scalable model for resource-constrained settings. Keywords: Maternal Health, Pharmacovigilance, Community Medicine, Obstetric Pharmacology, Patient Safety, Integrated Care.